Produção de nanofibras a base de Ecovio® associadas ao fármaco aceclofenaco e seu estudo de liberação in vitro - Carvalho, Bruno Marques (2019)
Aceclofenac is a non-steroidal anti-inflammatory drug, widely used to combat inflammation, especially in the joints. However, the excessive use by oral ingestion of this drug, due to its mechanism of action, which acts on the inhibition of cyclooxygenase enzymes (COX1 and COX2), can cause severe stomach pain and may even lead to bleeding. In order to avoid the first-pass metabolism and, consequently, the inhibition of these enzymes, new forms of drug release have been investigated, where systems with transdermal release have appeared with great prominence. For this type release, several polymer matrices are being studied, especially those capable of producing composite structures of nano or micro-fibers polymeric. One way of obtaining said material is by using electrospinning, which is a technique of producing nanofibrous structures by applying a high electrical voltage between the metal tip of a syringe containing the polymer solution and a metal shield, wherein the flow of the syringe fluid is controlled by an infusion pump. In this way, this work had as objective to produce membranes containing nanowires, by the technique of electrospinning, incorporating the drug aceclofenaco in its structure. For this, the experimental conditions for fiber production were investigated using poly (lactic acid) (PLA) and poly (butylene adipate) -co- (butylene terephthalate) (PBAT) polymers sold under the name Ecovio®. The membrane produced (15% m/v of Ecovio® in 85% chloroform:dimethylformamide with 15% m/m aceclofenac: Ecovio®) was characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential scanning calorimetry (CDE), Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction (XRD) the interaction between the drug and the matrix, through the appearance of bands characteristic of aceclofenac in the FTIR spectrum, and also the alteration of the thermal profile of the membrane, compared to another without the drug. In addition, the drug release profile was evaluated in vitro, simulating transdermal delivery conditions, in which the drug was quantified by an analytical method, developed and validated, by ultra-high performance liquid chromatography (UPLC) with detector by UV- Vis. The material produced released about 63% of the drug in 5 minutes and 100% in approximately 30 minutes. The release profile found was compared to different kinetic models of release, and the Weibull model was considered more adequate, by the R² adjusted criteria and Akaike criteria (AIC). Thus, the material developed has great potential for transdermal drug release and is suitable for transdermal delivery studies in vivo.